Transformacja systemowa gospodarki a polityka regionalna - Opałło, Mirosława (Wydział Prawa i Administracji UAM, 1992)
This paper presents two particular problems of regional policy, of great significance in a present-day situation in Poland, namely: 1) the processes of economic system in macroregional distribution, and 2) spatial aspects of the restructurization of industry. As to the first issue, special attention was paid to ownership transformations and the establishment of new economic entities, including joint venture companies. The analysis carried out in the article indicates, that ownership transformations of Polish economy are responsible for the growth of inter-regional differences. In those transformations preference is granted to well-developed regions, while weaker areas are being omitted. The second issue is illustrated by the sales structure and the employment measure in industry per 1000 persons. Both figures show unequal territorial distribution. The above analysis, referring to the years 1989 - 1991, shows that new regional policy is necessary. Areas and centres that require diversified adaptive activities should be distinguished, with optimum exploitation of self-regulatory potential of local communities.
System transformations of economy and regional politics